Implementation of Local Wisdom Based on Tolerance Character in Pancasila Village, Balun, Lamongan - Susandi, Ari; Inggar Dinanti, Regita; Mandala Putra, Andi (Lafadz Jaya Publisher, 2025)
Balun Village is one of the Pancasila villages in Lamongan Regency. There are three religions practiced by the village community, namely Islam, Protestant Christianity and Hinduism, they apply moderation and tolerance that varies between religious communities as part of the implementation of Pancasila values. Balun Village is located in Turi sub-district, Lamongan district. This village is often visited by Pancasila tourists from various circles, ranging from elementary school, middle school, high school students, even students who conduct research there. It is good in the village. The nickname of the village